White matter microstructure in bipolar disorder is influenced by the serotonin transporter gene polymorphism 5‐HTTLPR1. (March 2015) - Benedetti, F.; Bollettini, I.; Poletti, S.; Locatelli, C.; Lorenzi, C.; Pirovano, A.; Smeraldi, E.; Colombo, C.
Abstract : Bipolar disorder (BD) is associated with signs of widespread disruption of white matter (WM) integrity. A polymorphism in the promoter of the serotonin transporter (5‐HTTLPR) influenced functional cortico‐limbic connectivity in healthy subjects and course of illness in BD, with the short (s) allele being associated with lower functional connectivity, and with earlier onset of illness and poor response to treatment. We tested the effects of 5‐HTTLPR on diffusion tensor imaging (DTI) measures of WM microstructure in 140 inpatients, affected by a major depressive episode in course of BD, of Italian descent. We used whole brain tract‐based spatial statistics in the WM skeleton with threshold‐free cluster enhancement of DTI measures of WM microstructure: axial, radial and mean diffusivity and fractional anisotropy. Compared with l/l homozygotes, 5‐HTTLPR*s carriers showed significantly increased radial and mean diffusivity in several brain WM tracts, including corpus callosum, cingulum bundle, uncinate fasciculus, corona radiata, thalamic radiation, inferior and superior longitudinal fasciculus and inferior fronto‐occipital fasciculus. An increase of mean and radial diffusivity, perpendicular to the main axis of the WM tract, is thought to signify increased space between fibers, thus suggesting demyelination or dysmyelination, or loss of bundle coherence. The effects of 5‐HTTLPR on the anomalous emotional processing in BD might be mediated by changes of WM microstructure in key WM tracts contributing to the functional integrity of the brain. Abstract : White matter microstructure in bipolar disorder is influenced by a serotonin transporter gene polymorphism